WebAssembly as an alternative solution for JavaScript in developing modern web applications - Suryś, Dawid; Szłapa, Piotr; Skublewska-Paszkowska, Maria (Journal of Computer Sciences Institute, 2019)
The article describes the impact of using WebAssembly on the performance of web applications. A Blazor framework based on WebAssembly was used. The paper shows that it is possible to create fully functioning Single Page Application using C# programming language. The second application was made using Angular framework. Both applications implement the same functionalities. For prepared applications loading time and size of transferred data was measured. The impact of using browser cache memory and gzip compression was examined. The performance of handling http requests using GET and POST methods were measured. The performance of WebAssembly against JavaScript code in task of sorting a list of N objects was compared. The performance of modifying html DOM was examined. Selected code metrics of written applications were compared. JavaScript presents better performance with tasks related with browser API. WebAssembly was better for computing.